Abū Al-Ḥasan Muḥammad bin Yūsuf Al-‘Āmirī’s View on Religion - H Zuhri (Universitas Islam Negeri Mataram, 2016)
One of the thinkers on religion in Islamic philosophical discourse is Abū al-Ḥasan Muḥammad bin Yūsuf al-‘Āmirī (d. 381/933). His thoughts, written in al-i‘lām bi manāqib al-Islām as magnum opus for his intellectual carrier, have been identified as an ideal prototype of classical and rational religious studies. Before exploring the principles of religions, his first step was that he introduced the importance of knowledge of milliya or religiosities’ perspective for reading phenomena of religion. Apologetical-reflective was the common method used by al-‘Āmirī to read Islam and other religions. This method does not intend to disrespect or wrong other religions but it is as a tool to identify identity as well as distinguish Islam from other religions. However, al-‘Āmirī realised that epistemological, historic, or praxis problems in religion facts, including Islam, become homework for the next generation. DOI: http://dx.doi.org/10.20414/ujis.v20i1.803